2012
DOI: 10.1039/c2lc40401j
|View full text |Cite
|
Sign up to set email alerts
|

“Overpass” at the junction of a crossed microchannel: An enabler for 3D microfluidic chips

Abstract: Reported here is the design and fabrication of three-dimensional (3D) "overpass" microstructures at the junction of crossed microfluidic channels by femtosecond laser direct writing of photopolymers. The post-integrated overpass could be used for guiding different microfluids across the junction without mixing; therefore it is proposed as an enabler for achieving 3D microfluidic chips based on conventional two-dimensional (2D) microchannels. As representative examples, bi-crossed and tri-crossed microchannels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Microoptical components require high surface smoothness to guarantee their optical performance compared with other microcomponents. [16][17][18][19][20]30,31 Moreover, the flatness of the internal surfaces of the microchannels on which the components are created significantly affects their quality. Over areas measuring a few dozen microns on a side, the surfaces fabricated by FLAE have adequate optical quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microoptical components require high surface smoothness to guarantee their optical performance compared with other microcomponents. [16][17][18][19][20]30,31 Moreover, the flatness of the internal surfaces of the microchannels on which the components are created significantly affects their quality. Over areas measuring a few dozen microns on a side, the surfaces fabricated by FLAE have adequate optical quality.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used to integrate various 3D functional microdevices, [16][17][18][19][20] such as a microfilters, 16 mixers 18 or overpasses, 19 into a 2D microchannel for controllable filtering of particles, high-efficiency mixing of different solvents, and guiding of different fluids and cell migration, respectively. However, all these works concern the integration of mechanical devices or 3D models in microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TPP is generally used for integration of functional microcomponents into planar open microfluidic structures prepared using other techniques such as photolithography. Functional microfluidic systems that can perform controlled filtering of particles, high-efficiency mixing of different solvents, and individual guiding of different fluids have been successfully fabricated by the integration of TPPfabricated microfilters, 84 mixers, 69,85 and overpasses 86 into open microfluidic channels, respectively. A more detailed review of TPP applications for microfluidic device fabrication is available in Ref.…”
Section: F Functional Microfluidic Device Fabricationmentioning
confidence: 99%
“…Zhou et al [58] made a 3D channel structure through two-photon exposure of BSB-S 2 (2002); He et al [84] developed a method to build a 3D 'overpass' at the junction of crossed microchannels as a microchannel switch. Lindenmann et al [85] demonstrated a photonic chip-to-chip interconnection technique, named photonic wire bond (PWB), capable of linking nanophotonic SOI waveguides.…”
Section: Multiphoton Polymerizationmentioning
confidence: 99%